Autorytet nauczycielski w dobie PRL-u: założenia i rzeczywistość - Król, Joanna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This article was intended to analyse sense of a teacher authority in People’s Republic of Poland, especially relation between assumptions and reality. The findings reveal and emphasises thesis that an educational policy didn’t foster process of birth of real teacher’s authority. Official legal acts and practical ideological activities often forced many teachers to live in clash with their conscience and undermined their authority in pupil’s eyes. On the other hand, there are evidences that despite of political limitations some teachers were able to defend their position applying typical ways in PRL system: concealment, game of body language and direction protest against indoctrination.
Keywords: authority; indoctrination; teacher